OC-042 The development of a novel endoscopic orthotopic tumour model for oesophageal cancer. (22nd June 2015) - Sehgal, V; Butt, MA; Funnell, L; Pye, H; Khan, S; Puccio, I; Sultan, A; Woodhams, J; Mosse, S; Draper, B; Patrick, SP; Kalber, T; et al.
Abstract : Introduction: The incidence of oesophageal adenocarcinoma (OAC) continues to rise rapidly. A clinically relevant animal model of OAC is needed to help study the effectiveness of novel therapeutic strategies for OAC. Current animal models have many limitations. Models that involve the injection of cells into the flanks of rodents do not replicate the native environment of OAC. Surgical models producing permanent biliary reflux that can lead to cancer are limited by the need for highly skilled surgical techniques, difficult reproducibility and significant morbidity to the animals involved. We describe a novel orthotopic tumour model for OAC. Our model is based upon the injection of tumour cells into the rodent oesophagus under direct endoscopic visualisation. Method: Two human tumour cell lines were used – OAC (OE19) and colon adenocarcinoma (HT29). Both lines were stably transfected to express luciferase and maintained in 5% CO2 at 37 0 C. 6–8 week-old female nude athymic rats (RNU Rat) were used for all experiments. A high-resolution diagnostic endoscope was used to perform all endoscopic procedures. Animals were anaesthetised using Isoflurane with concomitant oxygen given. Under direct visualisation, OE19 or HT29 tumour cells were injected. Immediately after endoscopy, 1 ml of D-Luciferin (20 mg/ml) was injected i.p. to follow luciferase-expressing OE19/HT29 tumour implantation. After 15 min, rats were inserted into a whole body cooled charged-coupled device (CCD) camera Photon Imager system and images obtained. All animals had Bioluminescent imaging (BLI) and endoscopy performed regularly to look for evidence of tumour growth. Results: Implanted tumour cells were detected immediately after injection using BLI. Weekly, non-invasive BLI and regular endoscopic observation detected successful orthotopic tumour growth (Figure 1 ). Histological tissue samples confirmed the presence of tumour ulcerating the overlying squamous mucosa and infiltrating into, and through, the muscularis propria. This mirrors closely the behaviour of a primary human OAC. Conclusion: We have developed a novel, more clinically relevant, orthotopic tumour model for OAC. By utilising rodent gastroscopy, our model replicates the native environment in which OAC grows and provides an opportunity for us to better understand the natural history of OAC in a manner that confers considerably less morbidity to animals than current models allow. Disclosure of interest: None Declared.